DEMOGRAPHIC AUTHORITY AND ITS REGIONAL CHARACTERISTICS - ESHANKULOVA, DILBAR (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article analyzes the demographic potential of the Republic of Uzbekistan and its regional characteristics. Specific aspects of the number, structure and location of the country's population, regional differences in demographic processes have been studied. A comparison of regions was made according to the main indicators of demographic development. Recommendations on effective use of demographic potential have been developed. Based on the official data of the State Statistics Committee of the Republic of Uzbekistan, the number, composition and quality indicators of the population were analyzed and the role of the demographic potential in economic growth, innovative development and national security was thoroughly studied. Also, the in-depth analysis of demographic processes and the study of their regional characteristics are of urgent importance.